2004
DOI: 10.1002/cne.20168
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VIP and/or PACAP receptor mRNA in peptide synthesizing cells within the suprachiasmatic nucleus of the rat and in its efferent target sites

Abstract: The suprachiasmatic nucleus (SCN) contains the predominant circadian pacemaker in mammals. Considerable evidence indicates that VPAC(2) and PAC(1), receptors for vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating peptide (PACAP), play critical roles in maintaining and entraining circadian rhythms. Retinal projections to the rat SCN contain PACAP and terminate mostly in the ventral SCN, the site of VIP neurons. The incidence of VPAC(2) and PAC(1) mRNAs within distinct neuronal popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 122 publications
(211 reference statements)
5
47
0
Order By: Relevance
“…4 A and E and Fig. S9), as previously shown (15). A confocal z-stack analysis using triple labeling for VIP, a presynaptic marker (synaptophysin), and retinal axonal CTβ fluorescence revealed potential synaptic contacts between retinal axons and VIP+ neurons (Fig.…”
Section: Retinal Projections To the Scn: Identification Of Postsynaptsupporting
confidence: 80%
See 2 more Smart Citations
“…4 A and E and Fig. S9), as previously shown (15). A confocal z-stack analysis using triple labeling for VIP, a presynaptic marker (synaptophysin), and retinal axonal CTβ fluorescence revealed potential synaptic contacts between retinal axons and VIP+ neurons (Fig.…”
Section: Retinal Projections To the Scn: Identification Of Postsynaptsupporting
confidence: 80%
“…VIP+ cells are located in the ventral part of the SCN, in apposition with the optic chiasm, making these cells the best candidates for receiving light input. VIP+ cells send projections to the entire SCN, affecting the functions of other VIP+ cells and clock cells located in the shell of the SCN (15). Here, we showed that in mice ipRGCs form direct synaptic connections with VIP cells, but also with somas of AVP and GRP neurons.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…4 A). Consistent with the expression pattern of PACAP receptors (Kalamatianos et al, 2004), PACAP was also found to elicit pMSK1 expression in periventricular regions dorsal to the SCN. Discernable PACAPinduced pMSK1 expression was observed in 75% of the animals (n ϭ 8).…”
Section: Pacap-dependent Msk1 Activationsupporting
confidence: 73%
“…Studies have identified three candidate output signals, TGF-␣, cardiotrophin-like cytokine, and prokineticin 2, all of which inhibit locomotor activity (5,22,23). Vasoactive intestinal peptide (VIP) is a neurotransmitter expressed in many neuronal soma of the ventromedial SCN, which receives photic input from the retinohypothalamic tract (20). Processes from these neurons extend throughout the SCN as well as into the adjacent subparaventricular zone (SPZ).…”
mentioning
confidence: 99%